Utilizing Social Cognitive Career Theory to Enhance the Self-Efficacy and Outcome Expectations of Students with Disabilities Through Career Development. Issue 1 (9th May 2022) - Appling, Brandee; Tuttle, Malti; Harrell, Lindsay; Ellerman, Hillary; Mabeus, Danielle
Social cognitive career theory (SCCT) is a valuable framework when developing applicable and appropriate career development interventions for students with disabilities. The use of SCCT in developing interventions will enhance the self-efficacy and outcome expectations of K–12 students with disabilities, thereby leading to more purposeful, realistic, and positive career beliefs and behaviors. This article explores the self-efficacy and outcome expectations of students with disabilities and discusses possible interventions for school and college counselors.